Given that the function y = f (x) is an odd function on R, and when x > 0, f (x) = 1, then the expression of the function y = f (x) is______ .

Given that the function y = f (x) is an odd function on R, and when x > 0, f (x) = 1, then the expression of the function y = f (x) is______ .

Let x < 0, then - x > 0, f (- x) = 1 and function y = f (x) be an odd function on R, then f (- x) = - f (x) = 1, that is, f (x) = - 1. When x < 0, f (x) = - 1 according to function y = f (x) is an odd function on R, then f (- 0) = - f (0) = f (0), that is, f (0) = 0. In conclusion, the expression of function y = f (x) is f (x) = 1, (x > 0) 0, (x = 0) − 1, (x < 0), so the answer is: F (x) = 1, (x > 0) 0, (x = 0) − 1 ,(x<0)